The way of Steve Lacy : finding individuality through musical genealogy : a thesis and compositions towards a Master of Music in Composition at the New Zealand School of Music, 2012 - Johnson, Lucien (Massey University, 2012)
Abstract not available
Audio examples not included for copyright reasons
Keywords: Steve Lacy; Saxophonists; Jazz musicians; Jazz; Scores; Composition (Music); Improvisation; Music; Soprano saxophone